Implementasi Teknologi Chatbot sebagai Media Informasi di Universitas Negeri Medan - M Ikhsan; Dila Marta Putri; Siti Nurjanah; Asde Rahmawati; Fahrizal Fahrizal; Bastul Wajhi Akramunnas (Pusat Riset dan Inovasi Nasional, 2025)
Natural Language Processing (NLP) is a branch of Artificial Intelligence (AI) that deals with the interaction between computers and humans through natural language. In general, NLP is applied in various applications, such as language translators, for example Google Translate, and chatbots. This study will discuss further about chatbots with a software development approach using the System Development Life Cycle (SDLC) method. The dataset used in this study was obtained from the website of the State University of Medan (Unimed) and some additional information collected from third parties. Although the State University of Medan has implemented information technology, the response to questions received through the campus's online messaging service is still relatively slow, because until now these questions are still answered manually by the admin. The author and team pay attention to how a university provides information to students and prospective students regarding various questions about the campus and academic environment. Because problems were found in the information service system on the Unimed campus, the researcher provided an information service to solve this problem. This study resulted in an information service in the form of a chatbot for the State University of Medan, with an accuracy rate of around 70%. This chatbot is designed to operate through the Telegram messaging application, so it is expected to increase efficiency in responding to user questions.